Cancer Imaging - Elsayes, Khaled; Hicks, Rodney; Van den Abbeele, Annick D.; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
Cancer Imaging is an open access, peer-reviewed journal publishing original articles, reviews and editorials written by expert international radiologists working in oncology. The journal encompasses CT, MR, PET, ultrasound, radionuclide and multimodal imaging in all kinds of malignant tumours, plus new developments, techniques and innovations. Topics of interest include: Breast Imaging Chest Complications of treatment Ear, Nose & Throat Gastrointestinal Hepatobiliary & Pancreatic Imaging biomarkers Interventional Lymphoma Measurement of tumour response Molecular functional imaging Musculoskeletal Neuro oncology Nuclear Medicine Paediatric Theranostics.
Keywords: Oncology; Cancer; Imaging systems in biology; Nuclear medicine; Radiology; Oncology; Cancer Biology; Biological Imaging; Nuclear Medicine; Radiology